Use of Research as a Tool to Enhance Nuclear Security Education - Mostafa Kofi; Zenobia S Homan; Jason Timothy Harris; Lamiaa E Fiala Prof. (International Journal of Nuclear Security, 2023)
Introduction: Nuclear security education covers essential topics related to the security of nuclear materials. In order to provide effective training, educators are faced with the challenge of improving the trainees’ ability to retain and utilize knowledge. This project investigated whether academic research is beneficial for educators seeking to enhance nuclear security education. Methods: A survey using Google Forms was sent to nuclear security educators in academic and research institutes. The survey included questions on their experience with different aspects of nuclear security education, how research may influence nuclear security education, and how to increase knowledge retention. Results: In total, 45 people participated in the survey, with 71.1% of respondents from university settings and 13.3% from research institutes. Of these university and research institute respondents, 93.3% were members of the International Nuclear Security Education Network (INSEN), and 75.6% identified as educators. All participants indicated that research is important in order to enhance nuclear security education. Conclusion: Research on training and education in nuclear security can support trainees’ knowledge retention and application. Research is also useful for developing nuclear security training programs and curricula.
Keywords: Research; Nuclear security; Education